Total Wake: Natural, Pathological, and Experimental Limits to Sleep Reduction - Panchin, Yuri; Kovalzon, Vladimir M. (Frontiers in Neuroscience, 2021)
Sleep is not considered a pathological state, but it takes a third of a conscious human life. This share is much more than most optimistic life extension forecasts that biotechnologies or experimental and medical interventions can offer. Are there insurmountable physical or biological limitations on reducing the duration of sleep? How much can it be evaded without fatal consequences? What means can reduce the length of sleep? It is widely accepted that sleep is necessary for long-term survival. Here we review the limited, yet intriguing evidence that is not consistent with this notion. We concentrate on clinical cases of complete and partial loss of sleep and on human mutations that result in a short sleep phenotype. These observations are supported by new animal studies and are discussed from the perspective of sleep evolution. Two separate hypotheses suggest distinct approaches to remodel our sleep machinery. If sleep serves an unidentified vital physiological function this indispensable function has to be identified before “sleep prosthesis” (technical, biological or chemical) could be proposed. If sleep has no vital function but represent a timing mechanism for adaptive inactivity, sleep could be reduced by forging the sleep generation system itself with no adverse effects.